Remote and rapid pathological diagnosis in a resource challenged unit. Issue 6 (21st February 2014) - Carey, P; Fudzulani, R; Scholfield, D; Chagaluka, G; Tomoka, T; Liombe, G; Banda, K; Wadehra, V; Samarasinghe, S; Molyneux, E M; Bailey, S
Abstract : Malawi is one of the world's poorest countries, but despite this, has a dedicated paediatric oncology service. The service has been hampered by the inability to make a timely cytological diagnosis in the majority of patients. A telemedicine programme was commenced to help overcome this problem, and the results for the first 197 consecutive patients are described. The results are compared with the local reports where available. Most samples were fine needle aspirates (104/197–53%), but others included bone marrow aspirates, peripheral blood films and other fluid collections. A diagnosis was arrived at in 52% of the samples; there were 46 discordant results, 38 were when one or other of the local or distant teams were unable to make a diagnosis, and only 8 where the diagnoses of the 2 teams differed. Diagnoses were made and reports were compiled by the 'distant' team within 24 h and sent to the centre in Malawi. This simple telepathology initiative has had a positive impact on clinical management, and could be used in other less resourced centres twinned with better resourced ones.